DESIGNING A FINANCIAL ACCOUNTING INFORMATION SYSTEM SPREADSHEET-BASED - Zewindra Zai; Anton; Erli Suroningsih (RISTANSI: Riset Akuntansi, 2026)
This study aims to design an integrated accounting information system based on spreadsheets to support the process of recording transactions and preparing financial statements at CV Sukses Maju Jaya. The primary challenge identified is that transaction recording remains manual, resulting in less accurate and unstructured financial information. The research method used is descriptive qualitative with a Research and Development (R&D) approach. The results indicate that the system is able to automate the accounting cycle from journal entries to financial statements, including ledger, trial balance, income statement, statement of changes in equity, and statement of financial position. The system improves efficiency, accuracy, and supports better decision-making.